1999
DOI: 10.1074/jbc.274.33.22968
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Induction of Energy Gene Expression in Tissues of Mitochondrial Disease Patients

Abstract: We have examined the transcript levels of a variety of oxidative phosphorylation (OXPHOS) and associated bioenergetic genes in tissues of a patient carrying the myopathy, encephalopathy, lactic acidosis, and strokelike episodes (MELAS) A3243G mitochondrial DNA (mtDNA) mutation and the skeletal muscles of 14 patients harboring other pathogenic mtDNA mutations. The patients' tissues, which harbored 88% or more mutant mtDNA, had increased levels of mtDNA transcripts, increased nuclear OXPHOS gene transcripts incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
3
7

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 55 publications
7
100
3
7
Order By: Relevance
“…These findings contrast with observations in budding yeast cells where respiratory chain deficiency is followed by induced expression of genes that encode peroxisomal enzymes (6). In a previous study it was found that patients with different mtDNA mutations and rearrangements have an increased expression of genes encoding glycolytic enzymes in affected tissues (32). We found that the glycolytic enzyme activities do not directly correlate with the altered levels of gene expression, suggesting that there are posttranscriptional regulatory events involved.…”
Section: Discussioncontrasting
confidence: 55%
“…These findings contrast with observations in budding yeast cells where respiratory chain deficiency is followed by induced expression of genes that encode peroxisomal enzymes (6). In a previous study it was found that patients with different mtDNA mutations and rearrangements have an increased expression of genes encoding glycolytic enzymes in affected tissues (32). We found that the glycolytic enzyme activities do not directly correlate with the altered levels of gene expression, suggesting that there are posttranscriptional regulatory events involved.…”
Section: Discussioncontrasting
confidence: 55%
“…As usually occurs in mitochondrial disorders, the mtDNA depletion is associated with marked mitochondrial proliferation, a well known compensatory strategy for the reduced respiratory chain function. 18 The mtDNA depletion involves the muscularis propria of the entire GI tract and is most dramatically prominent in its external layer. In stomach and small intestine, the profound mtDNA depletion at this site correlates well with the observed atrophy and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…U p r e g u l a t i o n i n r e s i s t a n t s t r a i n s D o w n r e g u l a t i o n i n r e s i s t a n t s t r a i n s regulation of genes associated with ATP biosynthesis might point to inefficiencies of the energetic metabolism due to the mitochondrial degeneration in the Y-bearing spermatids that lead the upregulation of bioenergetic genes to compensate the energetic needs of the 'ill' cell (Heddi et al, 1999;Epstein et al, 2001). Altogether, the data support the notion that maternally and paternally inherited elements might genetically interact in the etiology of sex ratio distortion.…”
Section: F a T B O D Y C R O P M I D G U T H I N D G U T T U B U L E mentioning
confidence: 99%